Variation in the serum IgA concentration and the production of IgA in vitro in rheumatoid arthritis treated by sulfasalazine (1993)
Sulfasalazine is an efficient treatment for rheumatoid arthritis (RA), but its mode of action is not known. In RA, a correlation has been demonstrated between disease activity and the secretion of immunoglobulin A (IgA) by peripheral blood lymphocytes (PBL) in culture. Furthermore, the IgA-producing cells of the peripheral blood have been shown to originate from the mucous-associate lymphoid tissue (MALT). We studied the variations in the total IgA concentration in the serum of RA patients, and the secretion of IgA by PBL after 7 days culture in vitro, before and after treatment with sulfasalazine. A significant decrease in the serum IgA concentraton was obtained, but there was no modification of the spontaneous increase in the in vitro IgA synthesis by circulating monoclear cells. Our results suggested that the decrease in serum IgA concentration after treatment with sulfasalazine was not linked to a decrease in the IgA secretion by PBL. This does not favour a direct effect of sulfasalazine on the mucous-associated lymphoid tissue.